Conscious Sedation Efficacy of 0.3 and 0.5 mg/kg Oral Midazolam for Three to Six Year-Old Uncooperative Children Undergoing Dental Treatment: A Clinical Trial - Masoud Fallahinejad Ghajari; Ghasem Ansari; Leila Hasanbeygi; Shahnaz Shayeghi (Tehran University of Medical Sciences, 2016)
Objectives: Midazolam with variable dosages has been used to induce sedation in pediatric dentistry. The aim of this study was to compare the efficacy of two dosages of oral midazolam for conscious sedation of children undergoing dental treatment. Materials and Methods: In this randomized crossover double blind clinical trial, 20 healthy children (ASA I) aged three to six years with negative or definitely negative Frankl behavioral rating scale were evaluated. Half of the children received 0.5mg/kg oral midazolam plus 1mg/kg hydroxyzine (A) orally in the first session and 0.3mg/kg oral midazolam plus 1mg/kg hydroxyzine (B) in the next session. The other half received the drugs on a reverse order. Sedation degree by Houpt sedation rating scale, heart rate and level of SpO2 were assessed at the beginning and after 15 and 30 minutes. The data were analyzed using SPSS 19 and Wilcoxon Signed Rank and McNemar's tests. Results: The results showed that although administration of 0.5mg/kg oral midazolam was slightly superior to 0.3mg/kg oral midazolam in terms of sedation efficacy, the differences were not significant (P>0.05). The difference in treatment success was not significant either (P>0.05). Heart rate, oxygen saturation (SpO2) and respiratory rate were within the normal range and did not show a significant change (P>0.05). Conclusions: The overall success rate of the two drug combinations namely 0.5mg/kg oral midazolam plus hydroxyzine and 0.3mg/kg oral midazolam plus hydroxyzine was not significantly different for management of pediatric patients. Keywords: Conscious Sedation; Pediatric Dentistry; Midazolam; Hydroxyzine